(untitled) (Ameghiniana, 2014)
Upper Pleistocene glyptodonts from "Agua de Las Palomas", Campo del Pucara province of Catamarca, Argentina, are studied. The specimens consist in an almost complete carapace, a fragment of another carapace, and a ring of caudal armor; they are assigned to Glyptodon clavipes Owen, 1839, Glyptodon reticulatus Owen, 1845, and Glyptodon sp., respectively. Morphologic variations of the carapace scutes of Glyptodon reticulatus have been studied through the analysis of characters such as size and limit of scutes, number and distribution of foramina, number of peripheral figures and mean transverse diameter. The presence of Glyptodon reticulatus and Glyptodon clavipes suggests a Lujanian "Land Mammal Age" (Upper Pleistocene) for the fossiliferous levels at this locality.